2020
DOI: 10.3233/fi-2020-1910
|View full text |Cite
|
Sign up to set email alerts
|

On Orthogonal Projections on the Space of Consistent Pairwise Comparisons Matrices

Abstract: In this study, the orthogonalization process for different inner products is applied to pairwise comparisons. Properties of consistent approximations of a given inconsistent pairwise comparisons matrix are examined. A method of a derivation of a priority vector induced by a pairwise comparison matrix for a given inner product has been introduced.The mathematical elegance of orthogonalization and its universal use in most applied sciences has been the motivating factor for this study. However, the finding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In the theory of pairwise comparisons there are considered two groups K and L in A: K of multiplicative type and L ⊂ A of additive type. It should be noticed that all pairwise comparisons problems are originally stated for the multiplicative group K. Since these problems are extremely hard to solve even by computers [1], [3], [4], [10] and [11], they are approximated by additive projections onto L-valued consistent matrices, which are eventually transformed by using abstract exponential functions. Definition 1.…”
Section: Definitions and Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the theory of pairwise comparisons there are considered two groups K and L in A: K of multiplicative type and L ⊂ A of additive type. It should be noticed that all pairwise comparisons problems are originally stated for the multiplicative group K. Since these problems are extremely hard to solve even by computers [1], [3], [4], [10] and [11], they are approximated by additive projections onto L-valued consistent matrices, which are eventually transformed by using abstract exponential functions. Definition 1.…”
Section: Definitions and Preliminariesmentioning
confidence: 99%
“…e.g. [4], [10] and [1]) in an abstract setting, let K n×n be the set of all K-valued matrices M = [m ij ] n i.j=1 with entries in a multiplicative group K. Then K n×n is a multiplicative matrix group under the operation of pointwise multiplication of matrices M = [m ij ] and…”
Section: Consistent Matrices In Pairwise Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Problem outline. In [16] (a follow-up to [19]), Smarzewski has observed that PC matrices form a group under Hadamard product. In this paper, we will show that it is, in fact, a Lie group.…”
Section: A Is X Times [Comparison Operator] Than Bmentioning
confidence: 99%